The emerging role of oxidative stress in regulating autophagy: applications of cancer therapy - Zhang, W.; Wan, X.; Liu, Z.; Xiao, L.; Huang, H.; Liu, X. (Cellular and Molecular Biology, 2017)
Emerging evidences show that autophagy, as a major cellular adaptive degradation mechanism, is involved in tumorigenesis, cell aging, inflammation and neurodegeneration. It has been reported that multiple stresses including nutrient deprivation, pathogen infection, oxidative stress, endoplasmic reticulum (ER) stress and metabolic stress can influence cellular autophagy, leading to distinct cell fate. Although numerous studies have been employed to elucidate the probable issues, the underlying mechanism of the initiation and maturation of autophagy remains unclear. Herein, we discuss the possible cause and effect relationship between oxidative stress and autophagy, as well as the potential molecular mechanisms that oxidative stress may mediate the role of autophagy in cancer therapy, therefore shed some light on new therapeutic strategies of cancer.